A novel biomechanical system to intrude the upper incisors and control overbite: Posterior miniscrew-assisted lever arm and 2 cases report. Issue 47 (25th November 2022) - Zhang, Chenghao; Ji, Ling; Liao, Wen; Zhao, Zhihe
Abstract : Rationale: Overbite control is a key factor in orthodontic treatment. In some cases, incisor intrusion is essential and could be an optimal strategy for overbite control. The aim of this article was to introduce a biomechanical system called the posterior miniscrew-assisted lever arm, which is innovative in using existing posterior miniscrews to intrude the upper incisors and to control anterior overbite while simultaneously retracting the anterior teeth. Its efficiency in incisor intrusion has been proved with 2 cases. Patient concerns: Two adult women who came for orthodontic treatment with the chief complaint of convex profile were included in this study. Diagnosis: Both patients had similar malocclusions of Class II molar relationship, anterior deep overjet, and anterior deep overbite. Interventions: Their treatment plans were to extract 4 first premolars and insert 2 maxillary posterior buccal miniscrews. After teeth aligning and leveling, en masse retraction was started in both arches. During the space-closing stage, posterior miniscrew-assisted lever arms were placed in their upper arches so as to intrude upper incisors and control the overbite. Outcomes: After respectively 4 months and 3 months of incisor intrusion, the anterior overbite was successfully reduced to the normal range in each patient. Cephalometric analysis and superimposition also confirmed the treatment effect of this biomechanical system on incisor intrusion. Lessons: The posterior miniscrew-assisted lever arm is a valuable biomechanical system for intruding incisors and controlling anterior overbite.